Pengaruh Pengendalian Internal, Sumber Daya Manusia dan Sistem Informasi Akuntansi terhadap Good Governance di Kantor PEMDA Kabupaten Bengkulu Selatan - Febriani, Zhendrina; Perdanakusuma, Fathul Hilal; Seventeen, Winny Lian (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
This study investigates the influence of internal control, human resources, and accounting information systems on the implementation of good governance at the Regional Government Office of South Bengkulu Regency. The study is motivated by ongoing challenges in regional governance, particularly in areas with limited infrastructure and administrative capacity. The objective is to examine how these three organizational factors contribute to the effectiveness of public governance practices. Using a quantitative approach with a survey method, data were collected from 88 civil servants (ASN) selected through purposive sampling. The research employed multiple linear regression analysis to test partial and simultaneous effects. The results show that internal control and human resources significantly affect good governance, while the accounting information system does not have a significant individual effect. However, when analyzed simultaneously, all three variables show a significant influence. Among them, human resources have the most dominant effect. These findings highlight the importance of enhancing the quality and competence of public sector employees and strengthening control systems to improve transparency, accountability, and efficiency in local governance. This research contributes to the public sector accounting literature and provides practical recommendations for improving organizational management in regional governments.